Handbook of image and video processing - Bovik, Alan C. (Communications, Networking and Multimedia, 2005)
55% new material in the latest edition of this "must-have for students and practitioners of image & video processing!This Handbook is intended to serve as the basic reference point on image and video processing, in the field, in the research laboratory, and in the classroom.